Artificial Intelligence: Modulating BET Bromodomain Inhibitor ZEN‐3694 and Enzalutamide Combination Dosing in a Metastatic Prostate Cancer Patient Using CURATE.AI, an Artificial Intelligence Platform (Adv. Therap. 6/2018). Issue 6 (14th October 2018) - Pantuck, Allan J.; Lee, Dong‐Keun; Kee, Theodore; Wang, Peter; Lakhotia, Sanjay; Silverman, Michael H.; Mathis, Colleen; Drakaki, Alexandra; Belldegrun, Arie S.; Ho, Chih‐Ming; Ho, Dean
Abstract : The use of artificial intelligence and digital health has opened the doors to developing optimal treatment strategies for a broad spectrum of diseases. In article1800104, Allan J. Pantuck, Chih‐Ming Ho, Dean Ho and co‐workers harness the CURATE.AI platform for dynamic BET bromodomain inhibitor ZEN‐3694 and enzalutamide dosing. This AI‐guided treatment approach results in a durable response and halts disease progression in a metastatic castration‐resistant prostate cancer patient. Image credit: Zac Goh, National University of Singapore.